Kontraktledelse: Relasjonen mellom virksomhetsledelse og kontraktshåndtering, belyst via fire norske virksomheter - Jan Ole Similä (Copenhagen Business School (CBS), 2010)
– Why do we focus on the internal arrangements of the contractual process from a leadership perspective? Through empirical research where we have asked questions about the internal organizational arrangements, what kind of knowledge the organization need, and how institutional arrangements affect the contract process, we have tried to answer the main research question. We have also carried with us a question of if the organization's attachment to the public or private sector affects the arrangements. I have conducted a comparative case study where data has been generated from two public sector organizations, The National Road Administration, Helsebygg Midt-Norge, one private sector organization, Siemens, and one hybrid organization, NTE. Data was primarily generated from the governance system of the different organizations, and informant interviews. The analysis was carried out by two steps; first an empirical analysis, then a theoretical analysis, based on contractual theory, of the empirical findings. The empirical analysis shows that the organizations share the same thoughts on how to organize the contractual work; the division between the line and the project organization, the distribution of decision-making authority, and the institutionalization of a specific governance system. The organizational processes are formalized, and the governance system gives the clear recommendation on desired actions. The empirical data gives a clear understanding that the contract process is dominated by one profession — the engineers. Regarding the question on knowledge, I found the organizations to be interested foremost on problem solving competencies (engineering competencies). Other competencies, for example economic or legal competencies, where viewed as support competencies. We also found that personal skills in handling the complex and difficult processes and attitude toward ethics seemed to be of importance. On the question on how institutional elements in the organizational environment affected the contract process, we found that the overall interest of the organizations was stability and predictability. We also found that the market mechanisms cause the organizations some worry. In the end, the empirical findings did not give us any strong reasons to differentiate between public sector organizations and private sector organizations in how to deal with contractual work processes. The theoretical analysis has been carried out within classical and relational contract theory. The analysis shows that the empirical findings, to a great extend, can be explained through classical contract theory. It also gives us some ideas on what areas of the theory, especially relational contract theory that should be improved. Regarding the main research question, the conclusions indicate a need to establish a comprehensive approach to the contract process, to ensure a good balance between different partial processes. There also seem to be necessary to work on improvements on contract theory to increase the applicability of the theory, especially the relational contract theory.
hdl:10398/8011
Keywords: 650